Radiofrequency applicator for biomass heating (LACCEI, 2024)
In electromagnetic biomass processing, which has gained academic and industrial interest in recent years, an electromagnetic field interacts with the biomass, heating it. Its applications include the defrosting, cooking and pasteurization of food, the disinfestation of fruits, and the production of biofuels, among others. The main advantage of electromagnetic processing methods is that the heating takes place in the entire volume of the biomass to be treated in addition, it has great flexibility for its application in batch or continuous processing, resulting in faster and efficient processes. Although applications at microwave frequencies have recently received more attention than the radio frequency range, the latter has an important advantage: as the operating frequency is lower, the radiation penetration depth is greater, allowing more uniform heating and the possibility of processing larger volumes. This work presents the design, construction and electrical characterization of an electromagnetic heating system suitable biomass processing. From reflection coefficient measurements between 1MHz and 30MHz, an equivalent electrical model is developed and its parameters are determined. The operation of the system is described, with emphasis on the applicator.